Exploring Code Mixing Phenomenon by RRQ Lemon Case in Deddy Corbuzier’s Channel - I Wayan Agus Sutawan (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2026)
In the digital communication era, the phenomenon of code mixing is increasingly common, especially among public figures who interact with a wide and diverse audience. This study aims to explore the types and functions of code mixing used by RRQ Lemon, a well-known Indonesian e-sports player, during his interview on Deddy Corbuzier's YouTube channel. Using a qualitative descriptive method, the data were collected by transcribing and analyzing RRO Lemon's utterances from the video. The analysis was conducted based on the theories of Muysken (2000) and Suwito (1983), which categorize code mixing into insertion, alternation, and congruent lexicalization. The findings reveal that RRQ Lemon frequently mixes English and Indonesian in his speech, particularly in gaming-related contexts. The dominant type of code mixing found is insertion, with the main reasons being habitual use, the lack of equivalent terms in Indonesian, and audience adaptation. This study highlights how code mixing functions not only as a linguistic phenomenon but also as a strategy to shape identity and relate to a globalized digital audience.